Top-Tier Maternity and Children Specialist Smart Medical Care and Innovative 5G Outpatient Service Model. (14th June 2021) - Guo, ChaoRong; Zhu, Hui; Zhou, LiHua; Liu, YouQiong
Abstract : Purposes . Under the influence of big data, 5G technology, and the two-child policy, we are facing a shortage of medical resources, in short supply, and a substantial increase in demand for maternal and child health services. Medical needs improve patient experience, improve patient satisfaction, and apply smart medical care and 5G new model. Methods . Retrospective research methods and a large number of observation methods were used, and patient medical experience was improved through smart medical WeChat services, 5G technology, MDT (Multidisciplinary Team), one-stop services, and other measures. Research Results . Smart medicine and 5G models have effectively improved patient satisfaction and medical experience. Conclusions . Smart medicine meets the medical needs of women and children. 5G technology makes the medical model efficient and convenient and at the same time enhances the hospital's core competitiveness.